The Routledge handbook of archaeothanatology
1 online resource
Keywords: "The Routledge Handbook of Archaeothanatology spans the gap between archaeology and biological anthropology, the field and laboratory, and between francophone and anglophone funerary archaeological approaches to the remains of the dead and the understanding of societies, past and present. Interest in archaeothanatology has grown considerably in recent years in English-language scholarship. This timely publication moves away from anecdotal case studies to offer syntheses of archaeothanatological approaches with an eye to higher-level inferences about funerary behaviour and its meaning in the past. Written by francophone scholars who have contributed to the development of the field and anglophone scholars inspired by the approach, this volume offers detailed insight into the background and development of archaeothanatology, its theory, methods, applications, and its most recent advances, with a lexicon of related vocabulary. This volume is a key source for archaeo-anthropologists and bioarchaeologists. It will benefit researchers, lecturers, practitioners and students in biological anthropology, archaeology, taphonomy and forensic science. Given the interdisciplinary nature of these disciplines, and the emphasis placed on analysis in situ, this book will also be of interest to specialists in entomology, (micro)biology and soil science"--